Phosphodiesterase inhibitors roflumilast and vardenafil prevent sleep deprivation‐induced deficits in spatial pattern separation. Issue 6 (3rd March 2020) - Heckman, Pim R. A.; Roig Kuhn, Femke; Raven, Frank; Bolsius, Youri G.; Prickaerts, Jos; Meerlo, Peter; Havekes, Robbert
Abstract: Sleep deprivation (SD) is known to impair hippocampus‐dependent memory processes, in part by stimulating the phosphodiesterase (PDE) activity. In the present study, we assessed in mice whether SD also affects spatial pattern separation, a cognitive process that specifically requires the dentate gyrus (DG) subregion of the hippocampus. Adult male mice were trained in an object pattern separation (OPS) task in the middle of the light phase and then tested 24 hr thereafter. In total, we conducted three studies using the OPS task. In the first study, we validated the occurrence of pattern separation and tested the effects of SD. We found that 6 hr of SD during the first half of the light phase directly preceding the test trial impaired the spatial pattern separation performance. As a next step, we assessed in two consecutive studies whether the observed SD‐induced performance deficits could be prevented by the systemic application of two different PDE inhibitors that are approved for human use. Both the PDE4 inhibitor roflumilast and PDE5 inhibitor vardenafil successfully prevented SD‐induced deficits in spatial pattern separation. As a result, these PDE inhibitors have clinical potential for the prevention of memory deficits associated with loss of sleep. Abstract :